Fe Doped Titania Photocatalyst for Degradation of Methyl Orange - Muhamad Akif Aizuddin, Jasni; Devagi, Kanakaraju; Muhamad Hazim, Ya; Mohammad Sufian, Endra; Lim, Ying Chin (Elsevier Ltd., 2019)
Surface modification of titanium dioxide (TiO2) by doping method is one of the ways to lower TiO2 band gap and thus increasing its absorption to the visible region. This study was conducted to demonstrate a feasible modification of TiO2 by using iron (Fe) metal as the doping agent. Fe-doped TiO2 photocatalyst with the ratio of 1:1 was prepared by using the wet-impregnation method. The prepared photocatalyst was applied for the degradation of methyl orange (MO) under ultraviolet (UV) and visible light irradiation. A 0.20 g/L of Fe-doped TiO2 efficiently degraded 82.8% and 74.4% of 5 ppm MO under UV light and visible light irradiation, respectively. MO removal up to 85%was attained using bare TiO2 in the presence of UV compared to only 11% under visible light. The UV-Vis Diffuse Reflectance spectroscopy confirmed the reduction of TiO2 band gap upon Fe doping.